Endorectal Local Advancement Flap in Treating Rectovaginal Fistula-Our Experience in Bangabandhu Sheikh Mujib Medical University (Journal of Surgical Sciences, 2019)
Background: Rectovaginal fistula is abnormal epithelial-lined connections between the rectum and vagina. Rectovaginal fistula represents an often devastating condition in patients and a challenge for surgeons. Successful management of this condition must take into account a variety of variables including the etiology, size, and location of the fistula. Repair options include advancement flaps, plugs, fistula ligation, and tissue interposition.Method: We treated five cases of low rectovagianl fistula by endorectal local advancement flap in Colorectal Surgery Unit of Bangabandhu Sheikh Mujib Medical University between January 2011 to January 2014. Aim of this study was to evaluate the outcome of Endorectal local advancement flap in terms of cure, recurrence or failure in the management of rectovaginal fistula.Result: Out of five, four patients had rectovaginal fistula due to obstetric cause, one was post-surgical. One patient developed partial flap necrosis. The patient was managed by conservative means. Post-operative hospital stay was 5 days (range 4 -7 days). All patients achieved complete healing after the procedure.Conclusion: Rectovaginal fistula repair by endorectal local advancement flap should be part of the armamentarium of colorectal surgeons for treating persistent rectovaginal fistula.Journal of Surgical Sciences (2014) Vol. 18 (2) : 62-66